The ethics of sex - Thielicke, Helmut, 1908-1986.; Doberstein, John W. (New York : Harper & Row, 1964)
For here the sexuality of man is dealt with in broad context of Christian anthropology, in light of the doctrine of creation and redemption, of fellow humanity and the orders. And in order to familiarize the reader with this approach, the introductory section begins at once with a rather theoretical treatment of basic principles.
Introduction : the duality of man : biblical anthropology of the sexes -- Eros and agape : theological phenomenology of the human sex relationship. The problem : the interconnection of bios and person in the realm of eros ; The libido, animal and human ; The realization of the sex nature -- The order of marriage. The biblical interpretation of marriage ; The sacramental and the "worldly" interpretations of marriage; controversial theological considerations ; The changed position of woman in the family and in society (the problem of the equality of the sexes) ; Divorce and the remarriage of divorced persons -- Borderline situations. Birth control (the problem of optional sterility) ; Interruption of pregnancy (the problem of artificial abortion) ; Artificial insemination ; The problem of homosexuality.
"Constitutes a chapter ... [of the author's] Theological ethics."
Includes bibliographical references (pages 315-322) and index.
committed to retain from JKM Seminaries Library
commitment to retain
Keywords: Sexual ethics; Marriage; Sex -- Religious aspects; Sexual Behavior; Ethics; Marriage; Religion and Sex; Morale sexuelle; Mariage; Sexualité -- Aspect religieux; Sex -- Religious aspects; Marriage; Sexual ethics